Assessment of Heavy Metals as an emerging environmental pollutant in liver organs of Sheep and Goats from Erbil, Kurdistan Region of Iraq - Rebaz M. Mustafa; Hamadamin, Rawaz Rostam; Mamoon Q. Saleh; Amin, Abdulla A.; Obaidallah Hatam Yousif (Zanco Journal of Pure and Applied Sciences, 2023)
Bioaccumulation of heavy metals occurs in a variety of tissues in food animals as a serious environmental pollutant. The present study was to examine heavy metal levels such as Iron (Fe), Mercury (Hg), Manganese (Mn), Zinc (Zn), Arsenic (As), Cobalt (Co), Chromium (Cr), and Copper (Cu) in sheep and goat liver tissue from a polluted region in northern Iraq called Kurdistan. A comparison was made between all results and World Health Organization (WHO) standard limits. In this study, forty of samples tissue were taken from the livers of Sheep (n=20) and goats (n=20) from a slaughterhouse in Erbil, Kurdistan region north of Iraq. The concentration of eight vital heavy metals has been targeted by performing Inductively Coupled Plasma–Optical Emission Spectroscopy (ICP-OES) and concentrated HNO3 and H2O2 were used to dry and digest the samples. The result obtained from the study of heavy metals for instance (Mn, As, Zn, Co, and Cr) in the liver of sheep and goats is within the admissible limit recommended by World Health Organization (WHO). However, the remaining elements (Cu, Hg, and Fe) were found in danger, as they are higher than the normally accepted standards. Moreover, there is a significant difference for (Fe, Mn, Zn, Co, and Cr) and a non-significant for (Hg, As, and Cu) between the livers of sheep and goats in the study area. Variations in liver element values are likely attributable to feeding, environmental conditions, animal feed constituents, and analytical terms.